2020
DOI: 10.1142/s2010139221500051
|View full text |Cite
|
Sign up to set email alerts
|

Does Stock Liquidity Affect Corporate Debt Maturity Structure?

Abstract: We show an inverse relation between the use of short-term debt and stock market liquidity. This finding is robust to a battery of control variables, alternative measures of the key variables, and various identification strategies. A difference-in-difference (DiD) approach suggests that the relation between debt maturity structure and stock liquidity may be causal. The impact of stock liquidity on debt maturity is stronger in the presence of large institutional holdings and when borrowers are subject to greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…More recently, Marks and Shang (2017) found a strong linkage between short‐term debt and stock liquidity. Additionally, they also found that the use of short‐term debt and stock liquidity are substitute monitoring mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, Marks and Shang (2017) found a strong linkage between short‐term debt and stock liquidity. Additionally, they also found that the use of short‐term debt and stock liquidity are substitute monitoring mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, entry and exit in high liquid stock is easier and quite cheaper when compared to other stocks (Admati & Pfleiderer, 2009; Edmans & Manso, 2011). By this way the exit of large shareholders (block holders) may generate price pressure and may thereby pose as a threat to the earnings of managers, specifically when their compensation is linked to stock performance making it necessary for the manager to act in the best interest of the shareholders and making it less necessary to discipline the manager with debt market monitoring (Marks & Shang, 2017). All of these evidences suggest that high stock liquidity is associated worth the utilization of lower short‐term debt.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations